Reductive Effect of Acitretin on Blood Glucose Levels in Chinese Patients With Psoriasis - Qian, Hua; Kuang, Yehong; Su, Juan; Chen, Menglin; Chen, Xiang; Lv, Chengzhi; Chen, Wangqing; Zhu, Wu (Frontiers in Medicine, 2021)
Background: Psoriasis is a skin condition associated with increased risks of developing metabolic diseases, such as diabetes and hyperlipidaemia. Retinoid drugs, including acitretin, are commonly used to treat psoriasis due to its low cost and tolerable side effects. Objective: This study aimed to explore the influence of acitretin on patients’ metabolism levels, especially lipid and glucose. Methods: In this retrospective study, a total of 685 psoriatic patients and 395 age/sex matched controls were enrolled. The demographic and biochemical indexes of each participant were recorded. Acitretin (30 mg/d) combined with the topical ointment calcipotriol was used to treat the psoriatic patients, and the glucose and lipid profiles of patients before and after acitretin treatment were analysed. Results: The blood glucose levels of 685 psoriasis patients were significantly higher than that of the control group (P <0.001), while the blood lipid levels showed no difference between psoriatic patients and the matched controls. Triglyceride and low-density lipoprotein levels were significantly increased in 247 patients (P <0.05) after 8 weeks of treatment with acitretin. Interestingly, there was a remarkable downward trend in body mass index (BMI) and blood glucose levels (P <0.05) after acitretin treatment. Additionally, expression of both GLUT1 and GLUT4 in HaCaT and HepG2 cells were significantly increased when treated with acitretin. Compared to acitretin-free cells, the uptake of 2-NBDG was significantly higher in HaCaT and HepG2 cells after incubation with 5000 ng/mL acitretin for 36 h. Conclusion: Acitretin plays a significant role of reducing the blood glucose level in psoriasis patients. The mechanism of lowering blood glucose may be through increasing glucose intake by cells, thereby reducing glucose levels in the peripheral blood